Control of malting barley Fusarium head blight by bioagents - Gazdík, Zbyněk; Vymětal, Tomáš; Koprna, Radoslav; Lojková, Lea; Cerkal, Radim (KVASNY PRUMYSL, 2023)
The routine and prophylactic use of fungicides in cereals leads to increased aggressiveness of Fusarium infections. Cross-resistance to triazole compounds represents a significant health risk to both plants and humans. The application of some widely used fungicides causes increased production of DON. Residual concentrations of hydrophobic triazoles change chemical profile of malt and cause delayed fermentation with an impact on alcohol content. Increasing legislative restrictions of pesticide applications encourage the search for alternatives, starting with the overview of current state of knowledge on biological protection against Fusarium spp. Despite the fact that bioagents have been researched intensively, including field applications and several registrations, biological preparations for disease control against Fusarium head blight (FHB) of malting barley are not used on a mass scale. Generally, bioagents appear to be quite sensitive to environmental changes and soil variability, which causes problems with the evaluation of their effectiveness under field conditions. For efficient disease control of malting barley, the application based on biopreparations registered against FHB combined with weather prediction system can be recommended. With an emphasis on the occurrence of Fusarium graminearum as a key producer of deoxynivalenol (DON), the prediction system for malting barley should be employed from plant emerging to milk stage. When predicting a high incidence of the pathogen, chemical intervention must be considered. However, repeated application of bioagents in field conditions together with the implementation of bioagents directly into the malting process proved to be a promising way to decrease chemical interventions from the cultivation of malting barley.